Indian foreign policy: Agenda for 21st century; Vol.1 (Foreign Service Institute, 1997)
The two volumes of Indin Foreign Policy: Agenda for the 21st Century provide a perspective well as a projection of the challenges that lie ahead for India in the 21st century. They provide a platform for diverse perspective on national policy issues